2022
DOI: 10.1002/ajim.23428
|View full text |Cite
|
Sign up to set email alerts
|

Lost time: COVID‐19 indemnity claim reporting and results in the Wisconsin workers' compensation system from March 12 to December 31, 2020

Abstract: Background: The COVID-19 pandemic introduced a new compensable infectious disease to workplaces. Methods: This was a descriptive analysis of Wisconsin COVID workers' compensation (WC) claims between March 12 and December 31, 2020. The impact of the presumption law (March 12 to June 10, 2020) was also evaluated. Results: Less than 1% of working-age residents with COVID-19 filed a claim. COVID-19 WC claim rates (per 100,000 FTE) were notably low for frontline industry sectors such as Retail Trade (n = 115), Manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…54 In Washington, 1 of 2 states with an infectious disease presumption for frontline workers during a declared public health emergency, nearly 90% ( n = 17,792) of the 19,996 State Fund and self-insured COVID-19 claims submitted between February 2020 and August 2022 were accepted. 55 In an analysis of Wisconsin's COVID-19 WC claim denial rates during (March–June 2020) and after (June–December 2020) a presumption period in Wisconsin, Modji et al 50 found that the proportion of lost work time claims among first responders who were denied more than doubled from 18.4% to 43.8% when the presumption law was no longer in effect. Also, in an analysis of accepted COVID-19 claims from 11 states in the Midwest United States submitted to a large, private insurance carrier before August 31, 2020, Bernacki et al 56 found that the likelihood of filing a COVID-19 WC claim in a presumption state was significantly higher than in a nonpresumption state.…”
Section: Discussionmentioning
confidence: 99%
“…54 In Washington, 1 of 2 states with an infectious disease presumption for frontline workers during a declared public health emergency, nearly 90% ( n = 17,792) of the 19,996 State Fund and self-insured COVID-19 claims submitted between February 2020 and August 2022 were accepted. 55 In an analysis of Wisconsin's COVID-19 WC claim denial rates during (March–June 2020) and after (June–December 2020) a presumption period in Wisconsin, Modji et al 50 found that the proportion of lost work time claims among first responders who were denied more than doubled from 18.4% to 43.8% when the presumption law was no longer in effect. Also, in an analysis of accepted COVID-19 claims from 11 states in the Midwest United States submitted to a large, private insurance carrier before August 31, 2020, Bernacki et al 56 found that the likelihood of filing a COVID-19 WC claim in a presumption state was significantly higher than in a nonpresumption state.…”
Section: Discussionmentioning
confidence: 99%
“…42,59,60 In states with a presumption, COVID-19 claims accounted for 38% and 33% of total claims in Minnesota and Alaska during 2020, 31% of paid lost time claims in Michigan (2020-2021), and 19% of total lost time claims in Wisconsin during 2020. 45,50,54,61 This contrasts with nonpresumption states, where COVID-19 claims accounted for 10%, 9%, and 4% of total claims in Louisiana, New York, and Montana, respectively, during 2020. 41,44,55 Further, according to an analysis of over Washington, Alaska, and California awarded 89%, 79%, and 66% of all filed COVID-19 claims, respectively, and Michigan awarded 72% of COVID-19 indemnity claims with ≥7 days of lost work, despite differences in details of presumptive coverage.…”
Section: Covid-19 Compensation Presumptions Likely Led To Increased C...mentioning
confidence: 95%
“…Summaries are available 1,2 and state-based results have been described in individual state reports, [41][42][43][44][45][46][47][48][49][50] select multistate reports, [51][52][53] and a handful of peer-reviewed papers. [54][55][56][57][58] Without detailed analyses, state to state comparisons are difficult to make and limited in their interpretation given stark differences across states in economic responses to the pandemic, industry mix, presumption eligibility criteria, and presumption expiration dates. Keeping these limitations in mind, we identified several patterns that emerged from the patchwork of approaches to providing WC coverage for COVID-19.…”
Section: Rationale For a Covid-19 Presumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most prominent in recent years are SARS-CoV-2 and influenza viruses, especially among health care workers. 16 17 Tuberculosis is reported to have an occupational burden of 2.3 and 1% in silica-exposed workers and health care workers, respectively. 4 Community-acquired pneumonia among welders and zoonoses among workers with animal contacts also contribute to the burden of work-related infections.…”
Section: Occupational Respiratory Infectionsmentioning
confidence: 99%